2010
DOI: 10.1007/s11010-010-0677-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial adaptations in skeletal muscle to hindlimb unloading

Abstract: To gain insight into the regulation of mitochondrial adaptations to hindlimb unloading (HU), the activity of mitochondrial enzymes and the expression of nuclear-encoded genes which control mitochondrial properties in mouse gastrocnemius muscle were investigated. Biochemical and enzyme histochemical analysis showed that subsarcolemmal mitochondria were lost largely than intermyofibrillar mitochondria after HU. Gene expression analysis revealed disturbed or diminished gene expression patterns. The three main res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 69 publications
11
45
3
Order By: Relevance
“…Although we did observe some variability in mRNA expression levels of several OXPHEN regulators in response to hindlimb suspension, our finding that hindlimb suspension induced significant decreases in PGC-1␤ mRNA expression levels is in line with previous reports. In addition, we observed that unloading significantly decreased mRNA expression levels of Tfam and ERR-␣, which is in line with data from Wagatsuma et al who reported decreased expression levels of these regulators in soleus muscle of hindlimb-suspended rats (45). Interestingly, decreased expression levels of PGC-1 molecules and ERR-␣ are also observed in other models of disuse-induced loss of muscle OXPHEN such as denervation and spaceflight-induced gravitational unloading, suggesting that disuse of the musculature in broad terms initiates a conserved transcriptional program that leads to a coordinated downregulation of muscle OXPHEN (1,35,46).…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 92%
See 2 more Smart Citations
“…Although we did observe some variability in mRNA expression levels of several OXPHEN regulators in response to hindlimb suspension, our finding that hindlimb suspension induced significant decreases in PGC-1␤ mRNA expression levels is in line with previous reports. In addition, we observed that unloading significantly decreased mRNA expression levels of Tfam and ERR-␣, which is in line with data from Wagatsuma et al who reported decreased expression levels of these regulators in soleus muscle of hindlimb-suspended rats (45). Interestingly, decreased expression levels of PGC-1 molecules and ERR-␣ are also observed in other models of disuse-induced loss of muscle OXPHEN such as denervation and spaceflight-induced gravitational unloading, suggesting that disuse of the musculature in broad terms initiates a conserved transcriptional program that leads to a coordinated downregulation of muscle OXPHEN (1,35,46).…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 92%
“…Several studies have investigated the impact of unloading on expression levels of these regulators. Decreased expression levels of PGC-1␣ and PGC-1␤ but also of the PGC-1-related cofactor upon unloading have been consistently reported (23,27,45). Although we did observe some variability in mRNA expression levels of several OXPHEN regulators in response to hindlimb suspension, our finding that hindlimb suspension induced significant decreases in PGC-1␤ mRNA expression levels is in line with previous reports.…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 92%
See 1 more Smart Citation
“…Mfn1 and Mfn2 are the two key proteins on the outer membrane of mitochondria responsible for its fusion (34), while mitochondrial fission is mediated by Drp1 (15). Consisting with an earlier report (35), our results showed that the mitochondrial molecules involved in fusion and fission were repressed following unloading. These alterations suggested that mitochondria are less dynamic in disuse muscles.…”
Section: Hu Induced Muscular Mitochondrial Remodeling Characterized Bsupporting
confidence: 84%
“…For example, hindlimb suspension (Thomason and Booth, 1990), bed rest (Widrick et al, 1997) and denervation (Hornberger et al, 2001) are all accepted models for investigating decreased activity and disuse atrophy. Commonalities amongst these models are a decrease in muscle mass (Musacchia et al, 1983;Thomason et al, 1987), protein concentration (Bajotto and Shimomura, 2006;Larsson et al, 1996) and fiber size (Pellegrino and Franzini, 1963;Rittweger et al, 2005;Wagatsuma et al, 2011). Most studies also show a conversion from slow to fast fiber types (Boonyarom and Inui, 2006) and a decline in muscle strength (Adams et al, 2003;Larsson et al, 1996;Thomason and Booth, 1990).…”
Section: Muscle Plasticity In Non-hibernatorsmentioning
confidence: 99%